Pengaruh Hedonisme Influencer di Media Sosial Terhadap Perilaku Konsumtif Generasi Z di Daerah Istimewa Yogyakarta - Muhammad Lukman Hakim (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
Social media no longer functions merely as a means of interpersonal communication; instead, it creates a cultural ecosystem where trends, lifestyles, and self-identities are continuously reproduced and disseminated on a global scale. One of the most powerful manifestations of this transformation is the emergence of the